Situation of leisure and sustainable tourism in Costa Rica - Acuña Sossa, Mildred (2021)
The work presents an approach on the state of the leisure and sustainable tourism situation in Costa Rica, based on a series of category analyses such as: historic and heritage sites, programmed cultural activities, aquatic spaces, sites of cultural attraction, sites of natural attraction, tourist services or entertainment, recreation and leisure activities, adventure activities, natural and cultural education sites and rescue of wild animals. The purpose is to have a state of the situations affairs that guides the development of investigations and encourages timely management in various aspects such as: public policy, local plans or undertakings related to the search to reduce the gap that is eventually observed in the fulfillment of the universal right to leisure, recreation and tourism. The theoretical framework orients towards reflection sustainable tourism activity on, social tourism, destinations and what this economic activity implies in local economic development. The methodology used focused on bibliographic analysis and field work, which allowed a particular approach to the object of study. In the conclusion, it is highlighted that tourism implies access to a large number of people, who in principle should have the right to leisure, therefore, it is an activity for which people must be entitled to leisure of different social backgrounds. However, the accessibility to the different sites depends on a marked difference in the purchasing power of the people.